PENAMPILAN KLON DAN SEMAI DUA FAMILI Eucalyptus occidentalis BERTOLERANSI GARAM TINGGI DAN RENDAH PADA KONDISI TERGENANG DAN SALINITAS TINGGI - Rina Laksmi Hendrati (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2010)
Clonal materials are often collected for testing under extreme condition. Clonal production through mass vegegetative propagation is also common for deployment of improved genotype. Root development of clones compared to that of seedlings will further determine the subsequent growth. Eucalyptus occidentalis ability to grow under extreme conditions (waterlongging and/or salinity) drives the importance of provenance and family selection from materials collected throughout its natural distribution. Performance of clone and seedling under waterlogging and salt waterlogging conditions of two E. occidentalis families, high and low salt tolerant, were investigated. Seedling (4.5 months) and cutting/clones (5.5 months) were exposed to control, waterlogged and salt waterlogged conditions reaching to sea salt level (500 mM Nacl). Seeding and cutting performances were determined by ability of plant type and family to produce roots and consequently initial leaves to support their growth. Seedlings and cutting of high torelant family 153-Red Lake perform better than low tolerant family 96 Lake Magenta under high level of salinity. Under high salt concentration, seedling are better than cutting for family 153- Red Lake, but both plant types perform similiarly for family 96-Lake Magenta. Sanility hinders shoot and root development. Under inundation, E. occidentalis tends to decrease shoots rather than roots. For clonal growth improvement, propagation method to produce root abundance is necessary.